Understanding Hadith: Exoteric and Esoteric Dimensions by al-Ḥakīm al-Tirmiżī, al-Ghazālī, and Ibn al-‘Arabī al-Mursī - Akmaluddin, Muhammad (Jurnal Theologia, 2021)
The exoteric dimension is a systematic basis in looking for surface meaning of hadith. Whereas the esoteric dimension used to look for the unspeakable, the essential and the signal meaning. Understanding hadith meaning with both dimensions will explain the surface and deep meaning of hadith. By using qualitative approach, literary research and content analysis, this paper will discuss how the development of exoteric and esoteric dimensions in understanding hadith and both relationship. Each Islamic scholars has his own method when looking for the esoteric dimension in understanding hadith. Al-Ḥakīm al-Tirmiżī used proverbs (amṡāl), al-Ghazālī used consideration (i‘tibār), and Ibn al-'Arab Ibn al-‘Arabī used trainings (riyāḍāt) and struggles (mujāhadāt). Although using different terms, they agreed that the esoteric dimension must be based on the exoteric dimension. The detachment of the esoteric dimension from the exoteric dimension will cause the loss of the meaning foundation and will fall into bāṭiniyyah method.